Tool life of TiAlN PVD coated carbide tool in high-speed end milling of untreated inconel 718 under minimum quantity lubrication condition - Kasim, M.S.; Che Haron, C.H.; Ghani, J.A.; Gusri, A.I.; Yazid, M.Z.A.; Sulaiman, M.A. (Universiti Kebangsaan Malaysia, 2013)
This paper presents the tool life of the end milled Inconel 718, which is part of a material that is difficult to be machined. Previous researchers found that tool life in machining aged Inconel 718 is shorter compared with other materials. However, this observation required further investigation. Thus, a raw grade Inconel was proposed in this experiment. The experiments were performed using TiAlN-coated carbide. The studied milling parameters were the cutting speed, Vc, from 90 to 150 m/min; feed rate, fz, from 0.15 to 0.25 mm/rev; depth of cut, ap, from 0.3 to 0.5 mm; and radial depth of cut, ae=1 mm. The application of the cutting fluid used in this experiment was a minimum quantity lubricant, which had the advantage of cooling effectiveness and low consumption of cutting fluid. The results showed that the feed rate, fz, was the primary factor controlling the tool life. The combination of Vc=115 m/min, fz=0.15 mm/tooth, as well as ap=0.5 mm and ae=0.15 mm gave the longest tool life that served 95.38 min in operation.